(untitled) (PETITUM, 2021)
ABSTRACT: This study aims to determine the legal regulations implementation and law enforcement in supervision over fishing in Pangkep Regency. The research data is classified into 2 (two) types of data, namely primary data and secondary data. Data collection was carried out in 2 (two) ways, viz. library research methods and field research methods. After the relevant data is collected, the data is analyzed descriptively qualitatively, which describes the applicable laws and regulations related to legal theories and positive law enforcement practices that raise related issues. Based on the exposure of the research results, the authors then draw the following conclusions: (a) The implementation of legal regulations on the supervision of fishers in Pangkep Regency is carried out in several ways, namely the establishment of law enforcement arrangements for fishing activities in Pangkep Regency; (b) supervising marine and fishery resources for fishing in Pangkep Regency; (c) understand the forms of fishing violations in Pangkep Regency along with the implementation of supervision; (d) implement sanctions for fishing violations in Pangkep Regency. Then, the factors that affect the effectiveness of law enforcement in terms of supervision over fishing in Pangkep Regency are legal factors, law enforcement official’s factors, community factors, facilities factors, and cultural factors. ABSTRAK: Tujuan penelitian ini adalah guna mengetahui implementasi peraturan hukum serta efektivitas penegakan hukum dari segi pengawasan atas penangkap ikan di Kabupaten Pangkep. Penelitian ini tergolong jenis penelitian empiris. Pengumpulan data dilakukan dengan 2 (dua) cara yakni metode penelitian kepustakaan dan metode penelitian lapangan. Setelah data relevan dihimpun, maka data tersebut dianalisis secara deskriptif kualitatif yaitu menggambarkan peraturan perundang-undangan yang berlaku dikaitkan dengan teori-teori hukum dan praktek pelaksanaan hukum positif yang mengangkat permasalahan terkait. Berdasarkan paparan hasil penelitian, penulis kemudian menarik kesimpulan sebagai berikut: (a) Implementasi peraturan hukum terhadap pengawasan atas penangkap ikan di Kabupaten Pangkep dilakukan dengan beberapa cara yaitu pembentukan pengaturan penegakan hukum atas aktivitas penangkapan ikan di Kabupaten Pangkep; (b) melakukan pengawasan sumber daya kelautan dan perikanan terhadap penangkapan ikan di Kabupaten Pangkep; (c) memahami bentuk-bentuk pelanggaran penangkapan ikan di Kabupaten Pangkep disertai implementasi pengawasan; (d) melakukan penerapan sanksi pelanggaran penangkapan ikan di Kabupaten Pangkep. Kemudian, faktor-faktor yang mempengaruhi efektivitas penegakan hukum dari segi pengawasan atas penangkap ikan di Kabupaten Pangkep yaitu faktor hukum, faktor aparat penegak hukum, faktor masyarakat, faktor sarana, dan faktor kebudayaan.